POSS enhanced 3D graphene - polyimide film for atomic oxygen endurance in low earth orbit space environment - Shivakumar, Ranjana (2020)
Recently, 3D-graphene infused polyimide (3DC/PI) films have shown to be an effective protection coating for electrostatic discharge in spacecraft. However, these films are not suitable for Low Earth Orbit (LEO) due to atomic oxygen (AO) erosion. Here, we used Polyhedral Oligomeric Silsesquioxane (POSS) to enhance the AO durability of 3D-C/PI films. Three different ways of adding POSS to the composite films were studied with ground-based AO exposure. For all infusion approaches, their electrical conductivity behaviour is well preserved and the presence of POSS results in reduced AO erosion yield. Of all the methods studied here, incorporating POSS directly into PI results in the lowest erosion yield of 4.67 × 10−25 cm3/O-atom (one order of magnitude lower than that of Kapton). Adding POSS to PI, extends the durability of the composite film beyond 10 years, making it an ideal protective material for long term mission in LEO.